Applied shape optimization for fluids - Mohammadi, B.; Pironneau, Olivier (Oxford University Press, 2010)
Examining shape optimization problems for fluids, with the equations needed for their understanding and the simulation of these problems, this text introduces automatic differentiation, approximate gradients, and automatic mesh refinement.
Keywords: Fluid dynamics -- Mathematics.; Mathematical optimization.; Shape theory (Topology); elektronické knihy; electronic books